PELATIHAN BUDIDAYA JAMUR TIRAM SEBAGAI IMPLEMENTASI PERTANIAN PERKOTAAN DI KOTA PAREPARE - Syamsiar Zamzam; Mayasari Yamin; Sri Nur Qadri; Andi Dita Tawakkal Gau (LPPM Universitas Andalas, 2023)
The conversion of land into settlements is increasing every year, resulting in reduced agricultural land. The lack of agricultural land makes people in urban areas have to grow crops with urban farming concepts such as oyster mushroom cultivation. The concept of urban farming is one of the best solutions that can be implemented in a city like Parepare. Cultivating oyster mushrooms with the concept of urban farming is expected to increase people's income in Parepare City. This activity will be held at the Mushroom Cafe in March - April 2023. The formulation of this activity is that the people of Parepare City lack agricultural land and lack knowledge about urban farming. The purpose of this activity is so that people can apply the concept of urban farming by cultivating oyster mushrooms. This activity was carried out using 3 methods, namely: 1) socialization, 2) training and 3) practice. The stages of this activity are, 1) the community is given material on mushroom cultivation starting from preparing the tools and materials needed for harvesting and marketing, 2) the community is given the opportunity to practice directly accompanied by resource persons and 3) the community practices independently what has been given by resource persons. As a result of these activities, the people of Parepare City enthusiastically listened to every material presented and carried out hands-on practice. The conclusion from this activity is that the people of Parepare City are interested in applying the concept of urban farming with oyster mushroom cultivation.